Sistem Pendukung Keputusan untuk Menentukan Kegiatan Ekstrakurikuler Berdasarkan Bakat dan Minat Menggunakan Metode SAW (Simple Additive Weighting) - Yuda Irawan; Herianto; Susi Oustria Simamora (JTIM : Jurnal Teknologi Informasi dan Multimedia, 2019)
Extracurricular activities are an internal part of the learning process that emphasizes meeting student needs, extracurricular activities can be a means to channel talents and interests to encourage the development of potential students. In the extracurricular elections at the Taruna Satria Vocational School Pekanbaru is still manual where the extracurricular counselor is still based on self competence, but extracurricular determination is left entirely to students. So that a system is needed to improve the quality of good education. In making a decision there are many methods, and for the decision making for the selection of extracurricular activities at the Satuna Satria Vocational School, the SAW method (simple additive weighting) is used, the SAW method is a method used to find optimal alternatives from a number of alternatives with certain criteria. The solution obtained is that the application designed is a Decision Support System to Determine Extracurricular Activities Based on Interests and Talents in the Taruna Satria Vocational School Pekanbaru. This application can provide several advantages compared to the current system, which is efficient and effective in processing information and data management. With this application, it will help guide teachers and especially for students to choose extracurricular activities quickly and based on the talents and interests of these students